A zero-voltage conductance peak from weak antilocalization in a Majorana nanowire - D I Pikulin; J P Dahlhaus; M Wimmer; H Schomerus; C W J Beenakker (New Journal of Physics, 2012)
We show that weak antilocalization by disorder competes with resonant Andreev reflection from a Majorana zero mode to produce a zero-voltage conductance peak of order e ^2 / h in a superconducting nanowire. The phase conjugation needed for quantum interference to survive a disorder average is provided by particle–hole symmetry—in the absence of time-reversal symmetry and without requiring a topologically nontrivial phase. We identify methods of distinguishing the Majorana resonance from the weak antilocalization effect.